Associations of personal care products use with reproductive outcomes of IVF/ICSI treatment - Guo, Qing-Chun; Yao, Wen; Liu, Chong; Deng, Tao-Ran; Li, Juan; Liao, Hong-Mei; Tian, Wen-Qu; Wang, Yi; Du, Yao-Yao; Li, Yu-Feng (Frontiers in Endocrinology, 2024)
Introduction: Personal care products (PCPs) contain a number of endocrine-disrupting chemicals (EDCs) that could potentially affect the reproductive function in women of childbearing age. However, studies focused on the effects of PCPs use on reproductive outcomes are very limited. The current study aimed to explore the relationships between PCPs use patterns and reproductive outcomes in women undergoing in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) treatment. Methods: A total of 1500 women from the Tongji Reproductive and Environmental (TREE) study between December 2018 and January 2020 were included in this study. Participants provided characteristics of PCPs use within the previous three months. Retrieved oocyte number, mature oocyte number, two distinct pronuclei (2PN) zygote number, fertilization rate, cleavage rate, blastocyst formation rate, implantation, clinical pregnancy, miscarriage, and live birth were followed up as reproductive endpoints. Generalized linear regression model was utilized to assess the associations between various categories of PCPs use and reproductive endpoints of IVF/ICSI. Results: After adjusting for relevant covariates, women who used skin care products ≥14 times per week had a reduction of 22.4% in the maturation rate (95% CI: -39.2%, -1.6%) compared to participants who did not use skin care products. After transferring fresh embryos, women who used cosmetics 1–2 times per week (adjusted OR = 2.2, 95% CI: 1.0, 4.8) or 3–7 times per week (adjusted OR = 2.5, 95% CI: 1.2, 5.2) had a higher possibility of miscarriage than those who did not use cosmetics. There was negative association between the use of gel or soap and the cleavage rate among women aged < 30 years old (P for interaction = 0.01). Among women with BMI ≥ 24 kg/m2, the use of gel or soap was negatively associated with the blastocyst formation rate (P for interaction = 0.04), while cosmetics use was negatively associated with the maturation rate (P for interaction = 0.001). Conclusion: Our findings suggest that the use of PCPs in women of reproductive age have a potential adverse impact on IVF/ICSI outcomes, particularly skin care and cosmetic products.